The Coming Together of Times: Jean-Luc Godard’s Aesthetics of Contemporaneity and the Remembering of the Holocaust - Lund, Jacob (The Nordic Journal of Aesthetics, 2016)
This article reads Jean-Luc Godard’s film essay Histoire(s) du cinéma (1988–1998) as a contemporary artistic endeavour to resist the synchronising, standardising time of global capital, the pervasive uniformity of the global super-present, brought about by today’s televisual and digital communications, which threatens to trivialise the different processes of memory and history, as well as art and culture in general. Taking its point of departure in Bernard Stiegler’s observation that the final stage of capitalism is the control and synchronisation of “available brain time,” the article argues that Godard’s work opposes this control and synchronisation of our minds through an aesthetics of contemporaneity. The argument is based on the development of a theoretical framework that combines recent theories of contemporaneity with reflections on the politics of images. Focusing on the ways in which the Holocaust is remembered in Histoire(s) du cinéma, the article deals with Godard’s image-political creation of temporal contemporaneity through a montage of clips of old films and newsreels, photographs, stills, images of paintings, new footage, advertisements, music, sound and voice recordings, textual citation, narration and commentary.